International financial reporting standards (IFRS) disclosure and performance of Nigeria listed companies - N Grace Ofoegbu; Ndubuisi Odoemelam (Cogent Business & Management, 2018)
The study investigated disclosure practices under IFRS on the performance of firms listed on the Nigerian Stock Exchange for a period of six years, from 2012 to 2017. Data were pooled from 384 firm-year observations across 64 sampled companies listed in the Nigeria Stock Exchange (NSE). We developed disclosure index of both IFRSs mandatory and voluntary by applying content analysis and multiple regression techniques and analyze the association of disclosure and performance of the firms expressed return on capital employed (ROCE) as a performance index. The study also examined the relationship between market-based performance, company attributes, and overall disclosure. The result indicates that the extent of overall disclosure does not associate with the financial performance of the listed Nigerian firms. The result suggests that share price, size, and audit firm size significantly and positively related to the overall disclosure of firms. The association between leverage, company age and overall disclosure index negative and insignificant. In the Nigeria context, audit firm size proved to be an important determinant of the extent of IFRSs disclosure.